A study on the effects of emotional exhaustion and depersonalization on job satisfaction among CIMB Terengganu employees / Nor Hasniza Mat Hassan - Mat Hassan, Nor Hasniza (Faculty of Business and Management, 2018)
The main objective of this study is to investigate the effects of emotional exhaustion and depersonalization on job satisfaction among bank employees. This study was conducted among CIMB employees in the state of Terengganu, covering CIMB Jalan Sultan Ismail (Kuala Terengganu), CIMB Jerteh, CIMB Setiu, CIMB Dungun, CIMB AMBS, CIMB Gong Badak(UMT), CIMB Mesra Mall and CIMB Chukai. The items in the questionnaire are close ended type with a 5-point Likert scale. Through the survey made to the employees at the identified CIMB branch in Terengganu, a total of 140 set questionnaires were distributed. A total of 127 questionnaires were returned and the returned rate is 91%. The data collected for this study were analysed using Statistical Package for Social Sciences (SPSS), version 20. Pearson Correlation Coefficient and Multiple Regression were applied in analysing and interpreting the data. The result ofemotional exhaustion and depersonalization on job satisfaction generally support the hypotheses in this study. As conclusion, it can be said that the third objective of the study has been answered by the Coefficient Correlation in Pearson and Multiple regression had come to a conclusion where depersonalization gave the most significant factor that affect job satisfaction among the CIMB Bank employees in Terengganu instead of emotional exhaustion. Some of suggestions and recommendations were provided for future research in order to produce more accurate and comprehensive results for upcoming research